The cat sitter's whiskers - Clement, Blaize (Clement, Blaize. Dixie Hemingway mysteries., 2015)
"Pet sitter Dixie Hemingway is on the prowl again in the newest installment of Blaize Clement's classic and beloved series of cozy mysteries, now written by her son, John Clement, using Blaize's notes and ideas for future adventures. Set in the sleepy beach-side town of Siesta Key, Florida, THE CAT SITTER'S WHISKERS catches up with Dixie as she heads off for work one morning in the dimly lit hours before sunrise. Her very first client of the morning is Barney Feldman, a Maine coon cat with a reputation for mischief who's guarding his vacationing owner's valuable collection of decidedly creepy antique masks. But someone's hiding in the house when she arrives, and they sneak up and knock her out cold. When the cops arrive at the house, there's just one problem: no one has broken in and nothing is missing. Searching for answers, Dixie soon finds herself hopelessly trapped in a murky world of black market antiques, dark-hearted secrets, and murderous revenge... a mystery only she can solve. "--